Analisis Makna “Iiwake Suru” Dan “Benkai Suru” Dalam Website Surat Kabar Bahasa Jepang Asahi.Com - Felicia Felicia (Bina Nusantara University, 2011)
Verbs, particles, adjectives and conjunctions need to be understood well in learning Japanese. From a variety of verbs that exist, the author conducted an analysis of semantic field of the verbs